Analysis of Thinking and Language in the Cognitive Development of Santri Islamic Boarding School - Selamet Selamet; Faris Irfanuddin; Wantini Wantini (Early Publishing, 2025)
This qualitative field study investigated cognitive development among third-grade Madrasah Tsanawiyah students at Rumah Sajada Orphanage and Islamic Boarding School, Yogyakarta. Over five weeks the researcher observed seven pupils two selected purposively for detailed analysis during a one-hour formal lesson each week. Unstructured field notes were thematically analysed using Piaget’s Formal Operational Stage and the Islamic educational constructs of tadabbur, faqiha, and tadhakkur. Findings reveal a spectrum of formal-operational maturity: several students exhibited consistent abstract, deductive, and hypothetico-deductive reasoning, whereas others remained in transition. Routine tadabbur acted as a catalyst for executive-function growth, while adolescent egocentrism, manifested as an “imaginary audience,” occasionally constrained classroom discourse. Supportive teacher feedback and verse-based collaborative tasks reduced these barriers and promoted deeper reasoning. The study demonstrates that an integrated spiritual-academic environment can accelerate attainment of formal-operational competencies and enrich reflective language ability, providing empirically grounded recommendations for curriculum design in faith-based schools and similar educational contexts.